2021
DOI: 10.3390/mi13010026
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled 1-Octadecanethiol Membrane on Pd/ZnO for a Selective Room Temperature Flexible Hydrogen Sensor

Abstract: A layer of self-assembled 1-octadecanethiol was used to fabricate a palladium (Pd)/zinc oxide (ZnO) nanoparticle-based flexible hydrogen sensor with enhanced response and high selectivity at room temperature. A palladium film was first deposited using DC sputtering technique and later annealed to form palladium nanoparticles. The formation of uniform, surfactant-free palladium nanoparticles contributed to improved sensor response towards hydrogen gas at room temperature. The obtained sensor response was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Internal gas sensors in LIB should be flexible, stable under serious condition filling with electrolyte vapors and poor air, while operating at room temperature. Flexible gas sensors, including H 2 sensors, have been widely investigated [35,45,53,75,76].…”
Section: Internal Gas Sensors In Libsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal gas sensors in LIB should be flexible, stable under serious condition filling with electrolyte vapors and poor air, while operating at room temperature. Flexible gas sensors, including H 2 sensors, have been widely investigated [35,45,53,75,76].…”
Section: Internal Gas Sensors In Libsmentioning
confidence: 99%
“…Internal gas sensors in LIB should be flexible, stable under serious condition filling with electrolyte vapors and poor air, while operating at room temperature. Flexible gas sensors, including H2 sensors, have been widely investigated [35,45,53,75,76]. Lee et al [24] demonstrated that a PMMA membrane coating on Pd-graphene sensing layer could prevent the NO2, CO and CH4 response completely (Figure 11b).…”
Section: Internal Gas Sensors In Libsmentioning
confidence: 99%
“…Such wearable flexible gas sensors are usually composed of a flexible substrate, electrodes, and sensing materials, and can be applied in smart clothes, watches, masks, bands, human skin, joints, robots, etc., , which provides great convenience for human beings to open intelligent life and monitor harmful gases in real-time. Currently, it has been reported that flexible gas sensors with different sensing materials can realize various harmful gases such as ammonia (NH 3 ), nitrogen dioxide (NO 2 ), hydrogen sulfide (H 2 S), nitric oxide (NO), hydrogen (H 2 ), and ethanol , at room temperature. An ideal wearable flexible gas sensor requires excellent mechanical durability and sensing performance stability to well compromise the body movements or uncontrolled bending states.…”
Section: Introductionmentioning
confidence: 99%
“…The use of self-assembled monolayers (SAMs) has become a prominent method for surface modification due to the ease of formation via the binding of an adsorbate on a variety of different coinage metals (gold, silver, platinum, and palladium) and the robustness offered to the material by tailoring the interfacial properties of the films [10][11][12][13][14]. The most highly studied substrate for biological applications is gold due to its inert and biocompatible properties [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbate is composed of a headgroup (i.e., thiol [15][16][17], silane [18], imidazole [12], or phosphonate [19]) which can be adapted to bind to specific substrates. For gold and related noble metal substrates, thiol headgroups are typically used [13,16,20]. The second component of the adsorbate is a spacer, composed of an alkyl chain that dictates the packing of the resulting films through van der Waals (vdW) interactions [21].…”
Section: Introductionmentioning
confidence: 99%